2014
DOI: 10.1097/tp.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Neutralization of the Extracellular High-Mobility Group Box 1 on Renal Ischemia-Reperfusion Injury in Miniature Swine

Abstract: In this study, we demonstrated the beneficial effects of perioperative administration of anti-HMGB1 antibody in reducing renal IRI in a clinically relevant, large animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
(18 reference statements)
2
15
0
Order By: Relevance
“…Anti-HMGB1 antibody is reported to have a neutralizing effect on renal ischemia-reperfusion injury, and it also suppresses the number of apoptotic cells [25]. The results of this study show not only a reduction of apoptotic cells, but also a downregulation of JNK and TNF-α expression in kidney.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Anti-HMGB1 antibody is reported to have a neutralizing effect on renal ischemia-reperfusion injury, and it also suppresses the number of apoptotic cells [25]. The results of this study show not only a reduction of apoptotic cells, but also a downregulation of JNK and TNF-α expression in kidney.…”
Section: Discussionsupporting
confidence: 51%
“…Firstly, apoptosis has been reported to be involved in kidney damage at the cellular level after experimental CS [25, 30]. In fact, necrosis is also involved in kidney damage [25]. It is unilateral that we choose apoptosis to detect cellular survival status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, 3 One such insult is ischemia reperfusion injury (IRI). 4 IRI is an unavoidable complication in the process of cardiac transplantation, with the donor heart rendered ischemic for prolonged periods prior to implantation into the recipient and subsequent reperfusion. These processes damage the cardiac graft via activation of innate immune mechanisms, and the severity of this early inflammation and injury is associated with the ferocity and intensity of a subsequent adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 can be targeted in various ways, including inhibiting HMGB1 release, targeting HMGB1 directly, and blocking HMGB1 receptors. Both in vivo and in vitro studies found that in various pathological conditions, application of HMGB1 antagonists reduces inflammatory reactions [32][33][34]. It seems that interventions targeting the HMGB1-receptor axis provide more targets for treatment, which may be more amendable to the clinic.…”
Section: Intervention With Hmgb1 Antagonistsmentioning
confidence: 99%